Apolipoprotein ɛ4 breaks the association between declarative long-term memory and memory-based orienting of spatial attention in middle-aged individuals. (September 2016) - Salvato, Gerardo; Patai, Eva Z.; McCloud, Tayla; Nobre, Anna C.
Abstract: Apolipoprotein (APOE) ɛ4 genotype has been identified as a risk factor for late-onset Alzheimer disease (AD). The memory system is mostly involved in AD, and memory deficits represent its key feature. A growing body of studies has focused on the earlier identification of cognitive dysfunctions in younger and older APOE ɛ4 carriers, but investigation on middle-aged individuals remains rare. Here we sought to investigate if the APOE ɛ4 genotype modulates declarative memory and its influences on perception in the middle of the life span. We tested 60 middle-aged individuals recruited according to their APOE allele variants (ɛ3/ɛ3, ɛ3/ɛ4, ɛ4/ɛ4) on a long-term memory-based orienting of attention task. Results showed that the APOE ɛ4 genotype impaired neither explicit memory nor memory-based orienting of spatial attention. Interestingly, however, we found that the possession of the ɛ4 allele broke the relationship between declarative long-term memory and memory-guided orienting of visuo-spatial attention, suggesting an earlier modulation exerted by pure genetic characteristics on cognition. These findings are discussed in light of possible accelerated brain ageing in middle-aged ɛ4-carriers, and earlier structural changes in the brain occurring at this stage of the lifespan.